The first journal in exact sciences "Vestnik matematiėeskich nauk" - Libertas Klimka (Knygotyra)
The content, structure, and history of the first periodic journal of exact sciences in Russia, published by astronomer Matvei Gusev (1826-1866) in Vilnius from 1860 to 1863, are considered. The first volume contained 25 issues (198 pages) and the second one 16 issues (128 pages). Each issue was divided into four sections: original papers, bibliographic reviews, general reviews, and popular articles. The journal's subject matter included mathematics, mechanics, astronomy and geodesy, physics, and physical geography. The "Vestnik matematicheskikh nauk" is also a valuable source on the new astrophysical trends in research and the arrangement of Vilnius' observatory.